O estrangeirismo como fator de prestígio social ou estratégia de marketing em estabelecimentos comerciais de Curitiba - Magnani, Cristiane de Souza (2014)
This research is about the use of foreign terms in business establishments in the city of Curitiba. Wherever one looks at by walking along the streets of the big cities, one notes an increase of English names in all service and product lines. Thereby, the assumption is made that Brazil has received the influence of diverse cultures since its colonization, what justifies the amount of loanwords and foreignisms embedded into Brazilian Portuguese, as well as the choice for the theme. Therefore, the purpose of this paper is analyzing the occurrence of those terms in business establishments on the following social contexts in the city of Curitiba: Context A, represented by the Shopping Centers Barigui, Crystal and Mueller; and Context B, represented by the Shopping Centers Capão Raso, Cidade and Total. For understanding how business owners choose their shop’s names, this research begins with an approach of language, culture and identity concepts. Next, historical scenarios of Brazilian Portuguese are enabled and the constant language development is shown, due to the process of globalization and American acculturation. The difference between the terms “loanwords” and “foreignisms” is presented and there is how that resource is done as commercial strategy. Finally, it is shown the methodology used for analyzing the business establishment owners’ choice in the specific social contexts. A total number of 50 owners of each social context was selected to whom it was asked the reasons that have taken them to choose their shops’ names. The analysis of the answers allow to infer that the use of foreignism, especially the anglicisms, in naming the woman, man and child cloth and accessory stores takes place because of marketing strategy, followed by social prestigy. The results indicate that the amount of English terms overcomes the amount of other foreign and Portuguese terms.